2021
DOI: 10.1111/ases.12999
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green fluorescence‐guided laparoscopic deroofing of a liver cyst: A case report

Abstract: In performing laparoscopic deroofing (LD) of liver cysts, indocyanine green (ICG) fluorescent imaging is particularly useful for delineating adequate margins for the procedure and for avoiding duct injuries. However, the optimal timing of ICG injection has not yet been clarified. Herein, we describe a patient who had a large liver cyst, in whom safe and efficient LD was performed under sharp fluorescent imaging obtained by intravenous injection of ICG 1 hour before cyst fenestration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Recently, several studies have reported the use of ICG fluorescence imaging during LD (Table 1). 1–4 To the best of our knowledge, this is the first study summarizing LD using ICG fluorescence imaging for giant liver cysts. The mean maximum diameter of the cysts was 17.8 cm (range: 11.5–26 cm).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Recently, several studies have reported the use of ICG fluorescence imaging during LD (Table 1). 1–4 To the best of our knowledge, this is the first study summarizing LD using ICG fluorescence imaging for giant liver cysts. The mean maximum diameter of the cysts was 17.8 cm (range: 11.5–26 cm).…”
Section: Discussionmentioning
confidence: 95%
“…Recently, laparoscopic deroofing (LD) for symptomatic liver cysts has been accepted because of its less invasiveness of surgery and postoperative outcome. [1][2][3][4] In a recent systematic review of LD, good surgical results were reported, with a symptomatic relief of 90.2%, a symptomatic recurrence of 9.6%, and a reintervention rate of 7.1%. 5 However, conversion to open surgery during LD was necessary in 4.5%, mainly due to intraoperative bleeding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater omentum flap could contribute to local recurrence by reducing the size of the parenchymal opening and inducing adhesion[ 29 ]. Recently, laparoscopic liver cyst fenestration with indocyanine green (ICG) fluorescent imaging has been believed to be particularly useful for delineating adequate margins for the procedure and for avoiding duct injuries[ 30 - 32 ]. In this study, unroofing, followed mainly by fulguration of the cyst bed, led to no recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence imaging is a widely used method for bioimaging cells and tissues in vitro and in vivo, and also has promising applications for fluorescence‐guided surgery (Crawford et al, 2021; X. Li et al, 2021; Tanioka et al, 2021; Wolfbeis, 2015). Synthetic fluorescence probes and labels are used to make the sample of interest fluorescent.…”
Section: The Role Of Nanoparticles To Advance Imaging and Thermal Sen...mentioning
confidence: 99%